Dimensionality of a Coordination Polymer as a Tool To Control Thermal Expansion in a Polymorphic Coordination Compound. Issue 28 (26th July 2017) - Saha, Binoy K.; Rather, Sumair A.; Saha, Arijit
Abstract : Establishment of structure–property relationships is a subject of utmost importance in structural chemistry and materials science. The thermal expansion of strong bonds is known to be smaller than that of weaker bonds. Can this tendency be used to correlate the dimensionality of coordination polymers to their thermal expansion? In this study, we found that two 1D polymers of the polymorphic coordination complex of ZnCl2 and 4, 4′‐bipyridine exhibit much higher thermal expansion than the corresponding 2D polymer. This finding suggests that higher dimensionality can induce lower thermal expansion in coordination compounds. The thermal expansion has also been used here to explain the solid‐state phase transformation between the 1D and 2D structures. We anticipate that the dimensionality would be considered as an effective tool in designing new coordination polymers with desired thermal expansion properties and thermal expansion studies would be used in explaining solid‐state phase transformations in many cases. Abstract : Two 1D coordination polymers of ZnCl2 –4, 4′‐bipyridine complexes have much higher thermal expansions than that of the corresponding 2D polymer. Solid‐state‐to‐solid‐state phase transformation was observed between the 1D and 2D polymers. Here the dimensionality is used to control the thermal expansion, and the thermal expansion is used to explain the phase transformation in the material.